EPIDEMIOLOGY, CHARACTERISTICS, AND RISK FACTORS OF SURGICAL SITE INFECTIONS IN A TERTIARY CARE HOSPITAL IN WEST BANK: A RETROSPECTIVE COHORT STUDY - Jeetawi, Rawan (An-Najah National University, 2024)
Background: Surgical site infections (SSIs) are one of the major problematic complications that appear after surgery. These complications do not only impact patient recovery but also healthcare costs. Ultimately, SSI may result in prolonged hospitalization, excessive medical expenses, and, in the worst cases, death. Only by identifying the risk factors for SSIs, devising their effective prevention and management we can alleviate the issue and improve patients’ safety. Due to multiple administrative and technical challenges, the frequency is higher in developing nations, with estimates ranging from 2.5% to 41.9% globally. Nevertheless, data from Palestine is lacking. The goal of this study is to determine the incidence of SSIs for patients admitted to surgery at An-Najah National University Hospital (NNUH) during 2018–2020 in Nablus, Palestine, and associated risk factors. Methods: This is an analytical retrospective cohort study of all patients admitted for surgery between January 2018 and December 2020. 1157 patients were included. Sociodemographic and clinical data were gathered and analyzed using descriptive and analytical analysis accordingly and a binary logistic regression was performed to assess the potential risk factors associated with the development of SSI.A level of significance of 5% was used. IBM SPSS (Statistical Package for the Social Sciences) Version 21 was used to analyze the data. Results: A total of 1157 patients who underwent surgery procedures from 2018–2020 at NNUH had a total SSI incidence rate of 7.65%; the rate in 2018 was 18.2% decreasing to 6.6% and 0.6% in 2019 and 2020; Patients with prothesis implantation, longer-term procedures, and non-laparoscopic surgeries had higher incidence rates of SSIs (p≤0.05). In addition, those with an ASA index of IV or more were found to have a higher incidence of SSIs (p<0.001). The logistic regression found that surgeries with longer durations (more than 2 hours) are approximately 17 times more likely to result in an SSI (p<0.001), patients with a prosthesis are 9 times more likely (p = 0.002), and contaminated wounds are 23 times more likely to lead to an infection (p = 0.005). Moreover, each additional day a patient stays in the hospital increases the odds of developing an SSI by 4.6% (p<0.001). Conclusions The SSI surveillance program at NNUH revealed that minimizing surgery duration, managing blood glucose and temperature after surgery, and following the standard care bundle and infection control policies are vital for lowering the incidence of surgical site infections (SSIs). While these strategies can greatly enhance patient outcomes, additional research is necessary to evaluate their effectiveness across various surgical environments and patient demographics.
الانتشار الوبائي، مواصفات وخصائص والعوامل المؤدية لالتهابات وعدوى الموضع الجراحي في مستشفى الرعاية الثالثية في الضفة الغربية : دراسة بأثر رجعي